Systematic revision, molecular phylogeny and biogeography of the antlion tribe Acanthoplectrini (Neuroptera: Myrmeleontidae: Dendroleontinae), with emphasis on the Oriental lineage. (2nd August 2022) - Zheng, Yuchen; Badano, Davide; Liu, Xingyue
Abstract: The tribe Acanthoplectrini (Myrmeleontidae: Dendroleontinae) includes a group of antlion genera widely distributed across the Australasian and Oriental regions. The intergeneric and interspecific relationships between or within the Australian and Oriental lineages of this tribe as well as their historical biogeography remain largely unexplored. Here, we present a molecular phylogenetic and biogeographic analyses of Acanthoplectrini to infer the diversification history of this tribe, with emphasis on the Oriental lineage. Both the Oriental and Australian lineages are monophyletic and recovered as sister groups. Ancestral area reconstruction suggests that the ancestor of Acanthoplectrini might have been once widely distributed from Indochina to Australia and then split into the Oriental and Australian lineages during the early‐Miocene. Our analyses recovered northeastern Indochina and south China as the ancestral range of the Oriental Acanthoplectrini. During the mid‐Miocene to the mid‐Pliocene, orographic events such as the rising of mountain ranges (including the Himalayas) and the formation of major islands in southeastern Asia triggered several dispersal and vicariance events in the Oriental Acanthoplectrini, driving their speciation. We revise the classification of the Oriental Acanthoplectrini, establishing the new genus Paralayahima gen. n., which is recovered sister to Layahima Navás. Moreover, we describe four new species of Layahima, Layahima aspoeckorum sp. n., Layahima monba sp. n., Layahima lhoba sp. n. and Layahima xinliae sp. n., and we reinstate two previously synonymized species, Layahima melanocoris (Yang) stat. rev. and comb. n. and Layahima nebulosa Navás stat. rev. Abstract : We present the first systematic revision of the Oriental Acanthoplectrini and we reconstruct their phylogeny and biogeography based on mitochondrial and nuclear genomic data. We investigate the spatiotemporal divergence pattern between the Oriental and Australian lineages and the speciation events within the Oriental Acanthoplectrini. We provide a revised classification of the Oriental Acanthoplectrini, including 15 species of Layahima (four of which are new species) and establishing a new genus, namely Paralayahima  gen. n.